Vectors for efficient and high-throughput construction of fluorescent drosophila reporters using the PhiC31 site-specific integration system - Boy, Aurelia Lara; Zhai, Zongzhao; Kussler-Schneider, Yvonne; Kaspar, Petra; Lohmann, Ingrid (Genesis, 2010)
The fruit fly Drosophila is a leading model system for the study of transcriptional control by cis-regulatory elements or enhancers. Here, we present a rapid and highly efficient system for the large-scale analysis of enhancer elements, site-specifically integrated into the Drosophila genome. This system, which is scalable for either small projects or high-throughput approaches, makes use of the Gateway cloning technology and the PhiC31 site-specific integration system, which allows the insertion of constructs at predetermined genomic locations. Thus, this system allows not only a fast and easy analysis of reporter gene expression in live animals, but also the simultaneous analysis of different regulatory outputs on a cellular resolution by recombining in the same animal distinct enhancer elements fused to different fluorescent proteins. genesis 48:452-456, 2010. © 2010 Wiley-Liss, Inc.